2016
DOI: 10.1139/apnm-2015-0404
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal site-specific effects of endurance running on structure and strength of tibia, lumbar vertebrae, and mandible in male Sprague–Dawley rats

Abstract: Bone microarchitecture, bone mineral density (BMD), and bone strength are affected positively by impact activities such as running; however, there are discrepancies in the magnitude of these effects. These inconsistencies are mainly a result of varying training protocols, analysis techniques, and whether or not the skeletal sites measured are weight bearing. This study's purpose was to determine the effects of endurance running on sites that experience different weight bearing and load. Eight-week-old male Spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…A number of animal and human studies have shown that physical training induces changes in tibial bone density, microarchitecture, and geometry [25][26][27][28]. While using HR-pQCT to investigate differences in bone quality among alpine skiers (high impact), soccer players (moderate impact), swimmers (low impact), and control participants, Schipilow et al reported considerable differences in bone properties [29].…”
Section: Discussionmentioning
confidence: 99%
“…A number of animal and human studies have shown that physical training induces changes in tibial bone density, microarchitecture, and geometry [25][26][27][28]. While using HR-pQCT to investigate differences in bone quality among alpine skiers (high impact), soccer players (moderate impact), swimmers (low impact), and control participants, Schipilow et al reported considerable differences in bone properties [29].…”
Section: Discussionmentioning
confidence: 99%